2017
DOI: 10.1189/jlb.4a1216-513rr
|View full text |Cite
|
Sign up to set email alerts
|

BCL6 represses antiviral resistance in follicular T helper cells

Abstract: Follicular Th (Tfh) cells are a distinct subset of Th cells that help B cells produce class-switched antibodies. Studies have demonstrated that Tfh cells are highly prone to HIV infection and replication. However, the molecular mechanisms underlying this phenomenon are largely unclear. Here, we show that murine and human Tfh cells have diminished constitutive expression of IFN-stimulated genes (ISGs) inclusive of antiviral resistance factor MX dynamin-like GTPase 2 (MX2) and IFN-induced transmembrane 3 (IFITM3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…It is a key regulator gene in multiple myeloma [41,42]. BCL-6 has also been reported to be an antiviral resistance repressor in follicular T helper cells [43]. Hyper methylated In Cancer 1 (HIC1) is a transcriptional repressor that acts as a tumor suppressor and frequently is inactivated by epigenetic silencing.…”
Section: Discussionmentioning
confidence: 99%
“…It is a key regulator gene in multiple myeloma [41,42]. BCL-6 has also been reported to be an antiviral resistance repressor in follicular T helper cells [43]. Hyper methylated In Cancer 1 (HIC1) is a transcriptional repressor that acts as a tumor suppressor and frequently is inactivated by epigenetic silencing.…”
Section: Discussionmentioning
confidence: 99%
“…The IFITM1-3 genes are expressed in human lymphocytes, and IFITM1 is expressed at their cell surface, where it has been shown to associate with receptor signalling complexes. 12,[31][32][33] The IFITM family in T-cell differentiation and function…”
Section: Ifitm Expression In Human T Cellsmentioning
confidence: 99%
“…7,8 Interestingly, IFITM3 is also constitutively expressed in tissue-resident T cells in lung and airways, and also spleen, skin and brain, suggesting that it promotes their survival at these sites of potential viral infection. 8,12,13,37,53,69 Hence, several in vivo and in vitro studies have demonstrated the importance of IFITM3 in immunity to viral infection, by enhancing survival and viral resistance of immune effector populations, but these studies did not demonstrate an additional direct function of the IFITM proteins in the immune function of T cells or dendritic cells.…”
Section: Ifitm3 and Influenza Infectionmentioning
confidence: 99%
See 2 more Smart Citations